2021
DOI: 10.32523/ejpfm.2021050204
|View full text |Cite
|
Sign up to set email alerts
|

Study of structural and electronic properties of intercalated CrTiS2 compound by density functional theory

Abstract: In the present paper, we report the structural optimization of intercalated CrTiS2 compound by using Density Functional Theory (DFT) with Generalized Gradient Approximation (GGA) through Quantum ESPRESSO code. All the computations are carried out by using an ultra-soft pseudopotential. The effect of charge transfer from guest 3d transition metal Cr-atom to self-intercalated compound TiS2 has been studied. In electronic properties, the energy band structure, total density of states (TDOS), partial density of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Generally, the Density Functional Theory (DFT) is one of the foremost techniques based on the first principle. The time independent Schrödinger equation for many body systems like solids, nanomaterials and other complex systems can be solved efficiently with the help of DFT [17][18][19][20][21][22][23][24][25][26]. For solving the many body interactive systems, wave function method, viz.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the Density Functional Theory (DFT) is one of the foremost techniques based on the first principle. The time independent Schrödinger equation for many body systems like solids, nanomaterials and other complex systems can be solved efficiently with the help of DFT [17][18][19][20][21][22][23][24][25][26]. For solving the many body interactive systems, wave function method, viz.…”
Section: Theorymentioning
confidence: 99%
“…A few of them are Quantum ESPRESSO (Quantum open Source Package for Research in Electronic Structure, Simulation and Optimization) [31], SIESTA (Spanish Initiative for Electronic Simulations with Thousands of Atoms) [32], VASP (Vienna Ab-initio Simulation Package) [33], Wien2K [34], CASTEP (Cambridge Serial Total Energy Package) [35] and Abinit [36] etc. These codes have different implementation techniques for the calculation of properties and can be used to complement each other.The density functional theory (DFT) based formulation are found more useful for computing the structural and electronic properties of materials [17][18][19][20][21][22][23][24][25][26]. With the advantage of the electronic structure simulation based on density function theory (DFT), the present work mainly focuses on the electronic properties viz; electronic band structure, total electron density of states (DOS), partial DOS, integrated DOS and the Fermi surface study of -Uranium metal.…”
Section: Theorymentioning
confidence: 99%
“…Fang et al [3] have reported abinitio band-structure based calculations for bulk, single slab, and thin films of TiX2 (X=S, Se) using the localized spherical wave method. The density functional theory (DFT) based formulation are found more useful for computing the structural and electronic properties of materials [4][5][6][7][8][9][10][11]. The guest 3d atom have transferred the charge from transition metal Fe-atom to the self-…”
Section: Studies Of Transition Metal Dichalcogenides Compoundmentioning
confidence: 99%